Evaluace komunikační technologie UWB se zaměřením na bezpečnost - Hnátek, Michal (Vysoké učení technické v Brně. Fakulta elektrotechniky a komunikačních technologií, 2025)
Diplomová práce se věnuje evaluaci ultraširokopásmové (UWB) technologie se zaměřením na bezpečnostní aspekty. Práce zahrnuje teoretický rozbor UWB, relevantních standardů a bezpečnostních mechanismů. Hlavní částí jsou simulace v prostředí MATLAB, zaměřené na analýzu útoků na fyzickou vrstvu (Relay, Cicada) a vlivu rušení (Wi-Fi 6E, překážky) na kvalitu a dosah UWB komunikace. Výsledky jsou posouzeny s důrazem na porovnání komunikačních kanálů (CH2, CH3, CH5, CH9) a jejich implikace pro lokalizační systémy RTLS a standard omlox.

This master's thesis focuses on the evaluation of Ultra-Wideband (UWB) technology with an emphasis on security aspects. The work includes a theoretical analysis of UWB, relevant standards, and security mechanisms. The main part consists of simulations in the MATLAB environment, focused on analyzing physical layer attacks (Relay, Cicada) and the impact of interference (Wi-Fi 6E, obstacles) on the quality and range of UWB communication. The results are assessed with an emphasis on comparing communication channels (CH2, CH3, CH5, CH9) and their implications for RTLS localization systems and the omlox standard.
Evaluation of UWB communication technology focused on security
Keywords: IEEE 802.15.4z; lokalizace; MATLAB; omlox; RTLS; rušení; simulace; UWB; IEEE 802.15.4z; interference; localization; MATLAB; omlox; RTLS; simulation; UWB